Kadar kemanisan tebu (saccharum officinarum L.) di kampung Wariori Indah distrik Masni kabupaten Manokwari - Marlina Bitibalyo; Yohanis Amos Mustamu (Agrotek, 2021)
This study aimed to determine the level of sweetness of sugarcane growing in the village of Wariori Indah. This research was conducted in Wariori Indah village, Masni district, Manokwari regency in August 2020. The method used in this study was a descriptive method with field observation techniques. There were 5 types of sugarcane grown by the people of Wariori Indah Village, namely Red Sugar Cane (Meresa Ekeni), Yellow Green Sugar Cane (Meresa Ofrha), Yellow Sugar Cane (Meresa Oruk), White Striped Red Cane (Meresa Epsi), and Green Stripes Red Cane (Meresa Ofrha). The results of the study found that there were differences in the level of sweetness in the sugarcane plants observed. Yellow green sugarcane has a high level of sweetness (15.2), followed by yellow sugar cane (14.0), and red sugar cane (13.3), while white stripes red cane and green stripes red cane stripes having the same level of sweetness, namely 12.3.